The effects of enrofloxacin in combination of doxorubicin on cell viability in canine mammary gland tumor cells in vitro - Yang, Carolyn Kai-Ling (2017)
Mammary gland tumors are common among intact adult female dogs. Primary tumors can be surgically removed however, metastasis to lymph nodes and lungs can be present in advanced stages which is a common end point ultimately leading to death or decision for euthanasia. Chemotherapy using cytotoxic drug such as intravenous doxorubicin is delivered to dogs with advanced stages or with high grade adenocarcinoma tumors. The role of doxorubicin is to prevent distant metastasis and local recurrence, although cardiotoxicity is a common dose limiting side effect of this drug. Recently, enrofloxacin a bactericidal antibiotic agent was found to demonstrate anti-proliferative activity in human colon cancer and canine osteosarcoma cells in vitro. With this the hypothesis of this study is that enrofloxacin will reduce cell viability in a dose dependent manner and it will also enhance the cytotoxic effects of doxorubicin on canine mammary tumor cells. The objectives of this study are to determine the anti-proliferative effects of enrofloxacin in canine mammary tumor cell line, alone and in combination with doxorubicin. MTT and AO/PI assays were conducted on CMT-Stylo cells to determine cell proliferation and cell viability. Concentrations of doxorubicin (50nM, 100nM, 200nM, 400nM) and enrofloxacin (1, 3.125, 6.25, 12.5, 25, 50, 100 μg/mL) were chosen based on previous studies and IC50 for the cell line. Average of three replicate experiments in 96 well-plates for 24, 48 and 72 hours was determined and statistical analysis was done. There was reduced cell proliferation in cells treated with enroflocaxin alone or in combination with doxorubicin in a time and dose-dependent manner. The experiment concluded that the combination of these drugs has synergistic effects on canine mammary CMT-Stylo cells.